Development and Nutritional Assessment of a Weaning Food from Sorghum and Oil - Seeds - Lalude, L.O.; Fashakin, J.B. (Pakistan Journal of Nutrition, 2006)
The study investigated the use of locally sourced flours of germinated Sorghum, Sesame oil seed, Groundnut and Soyabeans which were combined in the ratio of 3 ½ : 1:1:1 (w/w), to produce weaning diet rich in energy and protein. The results showed significant differences (P< 0.05) between the experimental diet and a commercial weaning diet - “Nutrend” (Nestle, Nigeria) in terms of protein content, minerals and energy content . The experimental diet showed higher values when compared with the commercial diet. Also, the physico - chemical characteristics of the experimental diet were improved upon in terms of bulk - density, swelling capacity, viscosity and water - holding capacity. The animal feeding experiment further showed higher values of PER (Protein Efficiency Ratio) , FER (Food Efficiency Ratio) and Total tissue Nitrogen for the experimental diet. It was thus concluded that the experimental diet was capable of ameliorating Protein - Energy Malnutrition (PEM) in infants especially during the weaning period.